Reflection and mode conversion of surface acoustic waves studied by scanning acoustic force microscopy - Behme, G; Hesjedal, T (2001)
We present measurements of the reflection and mode conversion of surface acoustic waves (SAWs) by scanning acoustic force microscopy (SAFM). The SAFM offers a unique combination of high lateral resolution and high sensitivity towards acoustic modes of all polarizations. Since a SAW mixing experiment of two waves can be performed even if the amplitude difference between both waves is 40 dB, wavefields of extremely small amplitudes can be investigated. Using SAFM, the reflection of SAWs from a metallic wedge is investigated with submicron lateral resolution. We are able to identify two reflected wave modes, a Love and a non-coupling Rayleigh mode, by measuring their phase velocities.